Nadškof Alojzij Šuštar in Katoliška cerkev v Sloveniji v osemdesetih letih in v procesu osamosvajanja - Griesser Pečar, Tamara (Studia Historica Slovenica, 2022)
The paper, based on archival material from both the Archdiocesan Archives and the Commission for Relations with Religious Communities of the Republic of Slovenia, deals with the period from the takeover of the Ljubljana Archdiocese by Dr. Alojzij Šuštar until Slovenian independence. Despite being under the strict control of the Religious Commission and the political police, the Catholic Church became more present in the public sphere. The relationship between the state and the Slovenian Church changed with Šuštar's arrival, because he had a different approach and the authorities also changed their tactics, because the new archbishop had a high reputation abroad. The Archbishop tried to find common and acceptable solutions to the outstanding issues in relations between the State and the Church. The Slovenian Catholic Church supported the independence process, advocated for the plebiscite, and after the military attack on Slovenia, Archbishop Šuštar mobilized his excellent connections abroad.
Keywords: bishops; emancipation; history; Osamosvojitev; Plebiscit; plebiscite; Slovenia; Škofje; Šuštar, Alojzij; Zgodovina